An Investigation of the Teaching/Learning of the Oral/Aural skills in the Department of English at M’sila University - LEKBIR Ismahan, BOUBAAYA Samira (My University, 2018)
ABSTRACT The present is meant to study investigate the teaching/learning of the oral/aural skills of English department at M‟sila University. It attempts to shed light on the current situation of the teaching/learning of the two skills .The study aims at identifying the different strategies used by teachers and learners in order to enhance the speaking and listening skills. The dissertation also attempts to show the main difficulties that EFL learners and teachers face while learning and teaching the speaking and listening skills. The descriptive method was used based on two data collection tools. The questionnaire was administered to (60) EFL third year students because they have more experience in learning the two skills among the three years. Besides, the questionnaire was administered to (06) teachers of oral expression module to investigate the different opinions about the teaching/learning of the oral/aural skills. The findings showed that most EFL students and teachers encountered difficulties in oral course due to psychological problems (anxiety, lack of motivation, fear, and shyness); linguistic problems (lack of vocabulary, lack of knowledge of grammar ..) and pedagogical problems as the limited time which is allocated to oral expression module, also the lack of materials in teaching and learning the oral/aural skills. The study also showed the techniques and strategies that can be used by EFL teachers and learners to overcome their problems such as: free speech, group work. All of these findings are based on the theoretical part which is composed of two chapters, the first one is about speaking skill and its main aspects; the second chapter is about listening skill. In addition to, the practical part which includes one chapter discusses the analysis and the results of teachers‟ and the students‟ questionnaire. At the end of this study, some suggestions are proposed to improve the teaching /learning of both skills
Keywords: wordsKey wordsKey words Key words Key wordsKey words: Speaking skills, Listening skills